VD_FINDINFO Arrêt / 2025 / 236 vom 9. April 2025 - VD Tribunal cantonal (2025)
AIASSURANCE, ÉVALUATION DE L'INCAPACITÉ DE TRAVAIL, RENTE TEMPORAIRE, ATTEINTE À LA SANTÉ PHYSIQUE | 18 LAI, 28 LAI, 29 LAI, 4 al. 1 LAI, 8 LAI, 16 LPGA, 17 al. 1 LPGA, 6 LPGA, 7 LPGA, 8 al. 1 LPGA, 88a al. 1 RAI